2020
DOI: 10.1080/23320885.2019.1708203
|View full text |Cite
|
Sign up to set email alerts
|

A case of total scaphoid titanium custom-made 3D-printed prostheses with one-year follow-up

Abstract: A 34-year-old male patient developed scaphoid nonunion with necrosis in both fragments. A scaphoid replacement was performed using a titanium custom-made 3D-printed implant. At 1-year follow-up, good clinical and radiographic outcome was obtained. Titanium custom-made 3D-printed implants may offer a good surgical solution for patients requiring total scaphoid replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Patients with advanced Kienböck disease treated with an os lunatum excision followed by a titanium lunate replacement showed significantly improved wrist function and reported remarkable pain relief [ 47 , 48 ]. Several case reports have shown that customized 3D-printed implants, such as for the replacement of a nonunited scaphoid [ 49 ], a nonunited distal humerus [ 50 ], or the glenoid [ 51 ], are a safe and efficient alternative for the treatment of trauma-related injuries. In a case series of five patients, safety and efficacy of titanium ostheosyntheses plates for forearm osteotomies were evaluated [ 36 ] and, likewise, in a case of painful pseudarthrosis in the distal humerus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced Kienböck disease treated with an os lunatum excision followed by a titanium lunate replacement showed significantly improved wrist function and reported remarkable pain relief [ 47 , 48 ]. Several case reports have shown that customized 3D-printed implants, such as for the replacement of a nonunited scaphoid [ 49 ], a nonunited distal humerus [ 50 ], or the glenoid [ 51 ], are a safe and efficient alternative for the treatment of trauma-related injuries. In a case series of five patients, safety and efficacy of titanium ostheosyntheses plates for forearm osteotomies were evaluated [ 36 ] and, likewise, in a case of painful pseudarthrosis in the distal humerus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spingardi applied this total scaphoid titanium arthroplasty and even in cases followed more than 10 years observed no problems related to radial surface wear, carpal reabsorption cysts or intolerance to the implant material 9. More recently, Rosello applied a 3D-printed prosthesis of the scaphoid which was a copy of the prefabricated Sattel prosthesis which by that time was no longer available 10. The drawback of a prefabricated prosthesis is that it never fits perfectly.…”
Section: Discussionmentioning
confidence: 99%
“…9 More recently, Rosello applied a 3D-printed prosthesis of the scaphoid which was a copy of the prefabricated Sattel prosthesis which by that time was no longer available. 10 The drawback of a prefabricated…”
Section: Discussionmentioning
confidence: 99%
“…The same strategy has been implemented for total scaphoid replacement, following nonunion and necrosis in both fragments ( Fig. 3 m-o) [53] .…”
Section: Wrist (Scaphoid Bone)mentioning
confidence: 99%